ANALISIS PENGARUH TATA KELOLA PERUSAHAAN DAN KOMPENSASI EKSEKUTIF TERHADAP AGRESIVITAS PAJAK (Studi Empiris pada Perusahaan Nonkeuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2013–2016) - Siti Azizah Sofiati; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2018)
The purpose of this research is to analyze the effect of corporate governance structure (member of the board of commissioners and proportion of independent commissioners), executive compensation, and executive characteristic (president director tenure) on tax aggressiveness. Tax aggressiveness is measured by the Effective Tax Rate (ETR). The populations was nonfinancial companies listed on the Indonesia Stock Exchange (IDX) for the periode 2013-2016 with a total sampel of 224. The method of data collection used purposive sampling method. There are four independent variables included in this study: member of the board of commissioners, proportion of independent commissioners, executive compensation, and president director tenure. The primary tool of analysis used multiple linear regression analysis. The result of this research show that members of the board of commissioners has a negative effect and executive compensation has a positive effect on the level of tax aggressiveness. On the other side, the result show that proportion of independent commissioners and executive characteristic (president director tenure) do not influence of tax aggressineness.